Upaya Meningkatkan Kemandirian NU Ranting Wates Melalui Kerjasama Kelembagaan Antar Ranting NU di Kecamatan Tanjunganom - Saini, Mukhamat; Mufidah, Luluk Indarinul; Sujoko , Sujoko; Khoiriyah , Anatul; S, Nadia Amalinatus; Asmoro , Nur (Bisma : Bimbingan Swadaya Masyarakat, 2019)
The aim of this research is to analyze and evaluate the efforts made by the Nahdlatul Ulama (NU) Inter-Branch Institution in Tanjunganom District to improve the self-reliance of NU Wates Branch. The study focuses on the cooperation between NU branches in the district to enhance the independence of NU Wates Branch. The research uses a qualitative approach with data collected through observation, interviews, and document analysis. The results show that the cooperation between NU branches has been successful in improving the self-reliance of NU Wates Branch, particularly in terms of financial management, organizational structure, and community outreach. The study concludes that inter-branch cooperation is an effective strategy for improving the self-reliance of NU branches and strengthening the overall NU organization.